Civil adoption laws in Peninsular Malaysia / Norsidah Akashah - Akashah, Norsidah (Faculty of Law, 1982)
My main research and study are based mainly on the Civil Adoption Laws in Peninsular Malaysia namely : 1. Adoption Act 1952 2. Registration of Adoption Act 1952 Chapter one gives a brief legal history of adoption laws in England which was later implemented in the Straits Settlements as the adoption of Children Ordinance 1939* Later a Bill of the Adoption Act 1952 was introduced which was based upon the United Kingdom Act 1950 and which incorparated the 1959 Adoption of Children Ordinance to make one statutory provision applicable throughout the federation. This bill formed the backbone of the acts as they exist today. Wherelse chapter 2 mainly discusses the enforcement of both the acts namely the Adoption Act 1952 and the Registration of Adoption Act 1952. It also discusses briefly the procedure in court and the Registry Office for the adoption of children in Peninsular Malaysia. The third chapter is about a discussion on how adoption orders are made; who can adopt and be adopted. The consent requirement and dispensation of consent. Jn the fourth chapter, lays down the preliminaries to be satisfied before and after the adoption orders are made, inter alia, custody of the child, notice to the welfare department, appointment of guardian ad litem and functions of the court.